2019
DOI: 10.1149/2.0321908jes
|View full text |Cite
|
Sign up to set email alerts
|

MnO2-Coated Sulfur-Filled Hollow Carbon Nanosphere-Based Cathode Materials for Enhancing Electrochemical Performance of Li-S Cells

Abstract: When comes to very high energy density energy storage systems, the prospect of lithium-sulfur battery (LSB) technology is very promising. The major problem that prevents the commercial production of LSBs is their poor cycling life caused by the migration of polysulfide intermediates from the cathode structure to the anode. Confining sulfur and the discharged polysulfide intermediates inside conductive porous carbon matrices is regarded as a promising and effective strategy to overcome this problem. In this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…Between cycles 100 and 500, the AlF 3 ‐coated electrode has the excellent capacity retention of 88.9%, in contrast with 83.4% capacity retention for S@HCS. The long‐term cycling data is comparable and even better than the previous results obtained from S@HCS@MnO 2 nanocomposites …”
Section: Resultssupporting
confidence: 79%
“…Between cycles 100 and 500, the AlF 3 ‐coated electrode has the excellent capacity retention of 88.9%, in contrast with 83.4% capacity retention for S@HCS. The long‐term cycling data is comparable and even better than the previous results obtained from S@HCS@MnO 2 nanocomposites …”
Section: Resultssupporting
confidence: 79%
“…Figure 3 shows the result of the TGA analysis used to quantify the amount of infiltrated sulfur in the cathode. We targeted ~60 wt.% of sulfur loading because if too much sulfur was added, it could cover the outer surface of the carbon host and block the flow of Li + ions through the cathode structure [48]. TGA showed that sulfur was completely evaporated from the sample in the range of 150-400 • C in the amount of 63.4% of the mass of the sulfur-carbon composite.…”
Section: Resultsmentioning
confidence: 99%
“…The hosted active materials then possess smooth charge transfer capabilities and high material stability in the cathode [ 10 , 13 ]. The two main features of the carbon nanofoam, i.e., the conductive matrix that improves the reaction kinetics of sulfur [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ] and the porous network that enhances the electrochemical stability of the polysulfides [ 14 , 15 , 16 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ], are optimized by surface coating the carbon nanofoam with a layer of functional coating through chemical vapor deposition. This results in the formation of the graphene-coated and MoS 2 -coated carbon nanofoams that have a nanocoating attached on the carbon nanofoam substrates ( Figure 1 b,c).…”
Section: Resultsmentioning
confidence: 99%
“…To address these scientific issues, mainstream lithium–sulfur technologies are currently focused on optimizing the sulfur cathode [ 14 , 15 , 16 ] by the addition of conductive additives for high electrochemical utilization [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ] and by the inclusion of porous substrates for strong polysulfide stabilization [ 14 , 15 , 16 , 20 , 21 , 22 , 23 , 24 , 25 ]. One of the most promising methods is the synthesis of sulfur-based nanocomposites that have various conductive and porous substrates and can easily form composites with sulfur.…”
Section: Introductionmentioning
confidence: 99%